2012
DOI: 10.1007/s11136-012-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing self- and parent-reporting health-related quality of life in children with brain tumors

Abstract: Child-reporting of HRQOL is little influenced by the method of administration. Children's perception about HRQOL tended to be influenced by their trait anxiety, while parents' perception was influenced by their psychological distress, academic background, and their child's treatment status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…The present model shows a relationship between the child's BMI and its quality of life as perceived by the father, reflecting that the father perceives an excessive BMI as detrimental to his child's quality of life. Although a recent study reports no difference in the perception of the child's quality of life by the two parents (Sato et al, 2013), the moderate prediction that we find on the part of the father's perception could be due to the relationship we observed in the PA of father and child, perhaps indicating that fathers perform PA together with their sons, and hence have a better health perception of the latter. This study has certain limitations that merit consideration.…”
Section: Discussioncontrasting
confidence: 87%
“…The present model shows a relationship between the child's BMI and its quality of life as perceived by the father, reflecting that the father perceives an excessive BMI as detrimental to his child's quality of life. Although a recent study reports no difference in the perception of the child's quality of life by the two parents (Sato et al, 2013), the moderate prediction that we find on the part of the father's perception could be due to the relationship we observed in the PA of father and child, perhaps indicating that fathers perform PA together with their sons, and hence have a better health perception of the latter. This study has certain limitations that merit consideration.…”
Section: Discussioncontrasting
confidence: 87%
“…A cross‐sectional study by Aarsen et al found that older age at diagnosis was associated with poorer social QOL following low‐grade glioma. However, 7 other studies of varying sample size (n = 35‐142) found no significant relationship between age and QOL …”
Section: Resultsmentioning
confidence: 93%
“…There was excellent interrater agreement concerning the 8 methodological quality criteria ( κ = 0.91, P < .001). As shown in Table S2, 5 studies met 3 criteria, 3 met 4 criteria, 4 met 5 criteria, 5 met 6 criteria, 2 met 7 criteria, and 1 study met all 8 criteria . Most studies (>60%) adequately described sample characteristics, used representative sampling, reported descriptive data on SWB, controlled for potential confounds, and addressed selection bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations